Larvicidal effect of dried leaf extracts from Pinus caribaea against Aedes aegypti (Linnaeus, 1762) (Diptera: Culicidae) Efeito larvicida dos extratos de folhas secas de Pinus caribaea contra Aedes aegypti (Linnaeus, 1762) (Diptera: Culicidae) - Luiz Alberto Kanis; Rodrigo Damian Antonio; Ériston Paes Antunes; Josiane Somariva Prophiro; Onilda Santos da Silva (Revista da Sociedade Brasileira de Medicina Tropical, 2009)
In this study, the larvicidal activity of dried leaf extracts from Pinus caribaea Morelet against Aedes aegypti was evaluated for the first time. Pinus caribaea extracts were obtained by macerating dried leaves in alkaline hydroethanol, ethanol and acetone solutions followed by evaporation under reduced pressure. The lignin content was quantified using the thioglycolic acid complexation method. Lethality bioassays (LC50 and LC90) were carried out in accordance with the recommendations of the World Health Organization. The results showed that the acetone extract from Pinus caribaea was more active, and that larvicidal activity was associated with lignin concentration. Neste trabalho foi avaliada pela primeira vez a atividade larvicida contra Aedes aegypti de extratos obtido a partir de folhas secas de Pinus caribae. Os extratos de Pinus caribaea foram obtidos a partir da maceração de folhas secas em solução hidroetanólica alcalina, etanol e acetona, seguido de evaporação sob pressão reduzida. O teor de lignina foi quantificado usando o método de complexação com ácido tioglicóliclo. Os ensaios de letalidade foram conduzidos de acordo com a recomendação da Organização Mundial da Saúde. Os resultados demonstraram que o extrato obtido com acetona foi mais ativo, e a atividade larvicida esta associada com a concentração de ligninas.